The relationship between student's perceptions of the learning environment with learning outcomes of the immune system in distance learning - Fitria Nur Cahyati; Mieke Miarsyah; Sri Rahayu (Biology Education Department, IKIP Budi Utomo, Malang, Indonesia, 2022)
Students' perception of the learning environment is the process of students interpreting the learning experiences they receive. The learning environment is an external factor that has an important role in the learning process, namely as a place to facilitate students and teachers in achieving learning goals. Therefore, it is necessary to have a good learning environment so that the learning process runs smoothly and students' perceptions of the learning environment become positive because this is related to student learning outcomes. This study aims to determine the relationship between student's perceptions of the learning environment with learning outcomes of the immune system in distance learning. This research was conducted at SMA Negeri 21 Jakarta in June of 2020/2021. The method used was quantitative with a correlational study. The sample in this study was 105 students of class XI MIPA who were selected by simple random sampling. The research instrument for students' perceptions of the learning environment uses the Dundee Ready Education Environment Measure (DREEM) questionnaire with a measurement scale, namely the Likert scale. In contrast, the immune system learning outcome instrument in distance learning is a test based on basic competence (KD) and competency achievement indicators (GPA). The test is in the form of multiple-choice with five answer choices. Giving a score for each question if it is correct, will get a score of 1 and if the answer is wrong it will get a score of 0. The prerequisite Test shows the data is normally distributed and homogeneous. Based on the statistical hypothesis testing results, a significant regression model and the correlation coefficient have a strong relationship. Furthermore, the coefficient of determination was calculated and the R Square value was obtained which indicated that students' perceptions of the learning environment were related to the learning outcomes of the immune system in distance learning.